Hollows of a science of consciousness? - Pereira Júnior, Alfredo [UNESP] (My University, 2010)
I consider Nixon’s essay a well thought discussion of the possibility of a genuine science of consciousness. Most of the sections are worth discussing, but to find the main message it may be necessary to read between the lines. The good news is that he does not present true impossibilities for this science, but his discussion leads to the (sound) conclusion that it would have to account for many unconscious factors that make us creative and human.
Keywords: Consciousness; Science; Hollows